2008
DOI: 10.1038/leu.2008.323
|View full text |Cite
|
Sign up to set email alerts
|

Association of drug metabolism gene polymorphisms with toxicities, graft-versus-host disease and survival after HLA-identical sibling hematopoietic stem cell transplantation for patients with leukemia

Abstract: Individual differences in drug efficacy or toxicity can be influenced by genetic factors. We investigated whether polymorphisms of pharmacogenes that interfere with metabolism of drugs used in conditioning regimen and graft-versus-host disease (GvHD) prophylaxis could be associated with outcomes after HLA-identical hematopoietic stem cell transplantation (HSCT). Pharmacogenes and their polymorphisms were studied in 107 donors and patients with leukemia receiving HSCT. Candidate genes were: P450 cytochrome fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 61 publications
2
81
0
2
Order By: Relevance
“…Of all methotrexate's candidate genes previously examined, MTHFR, in particular the non-synonymous C677T (rs1801133) and the A1298C (rs1801131) polymorphisms, has received great attention but yielded conflicting results. 18,23,24,[29][30][31]46 In this study, associations were found between MTHFR genetic status and grade II-IV acute GvHD; none, however, remained positive for severe acute GvHD after correction for multiple testing. Based on our data, it is suggested that the SNP associated with grade II-IV acute GvHD herein are either: (i) associated with a less severe form of the disease (grade II), and/or (ii) the lower MAF (<20%) of these variants did not allow us to demonstrate their associations with grade III-IV acute GvHD occurring at a frequency of 15% in our cohort.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Of all methotrexate's candidate genes previously examined, MTHFR, in particular the non-synonymous C677T (rs1801133) and the A1298C (rs1801131) polymorphisms, has received great attention but yielded conflicting results. 18,23,24,[29][30][31]46 In this study, associations were found between MTHFR genetic status and grade II-IV acute GvHD; none, however, remained positive for severe acute GvHD after correction for multiple testing. Based on our data, it is suggested that the SNP associated with grade II-IV acute GvHD herein are either: (i) associated with a less severe form of the disease (grade II), and/or (ii) the lower MAF (<20%) of these variants did not allow us to demonstrate their associations with grade III-IV acute GvHD occurring at a frequency of 15% in our cohort.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, it is recognized that the genetic diversity of xenobiotic/drug metabolizing enzyme genes together with clinical factors could partly predict the development of GvHD and several candidates have been identified from hypothesisdriven studies, 7,[9][10][11][16][17][18][19][20][21][22][23][24] Effective immunosuppression is mandatory to prevent graft-versus-host disease and to achieve a successful clinical outcome of hematopoietic stem cell transplantation. Here we tested whether germline single nucleotide polymorphisms in 20 candidate genes related to methotrexate and cyclosporine metabolism and activity influence the incidence of graft-versus-host disease in patients who undergo stem cell transplantation for hematologic disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, some studies have addressed the impact of polymorphisms in ATP binding cassette (ABC) transporters on the toxicity of imatinib, vincristine or mitoxantrone, albeit with contradictory results (Cotte et al, 2009;Gurney et al, 2007;Hartman et al, 2010;Plasschaert et al, 2004). In addition, polymorphisms in drug-metabolizing enzymes such cytochrome P450 (CYP) 2B6 or CYP2D6 may also be involved in the occurrence of adverse effects in response to treatments including imatinib, cyclophosphamide and etoposide (Gardner et al, 2006;Kishi et al, 2004;Rocha et al, 2009). However, these results are far from being consistently demonstrated and further studies are needed to elucidate whether these polymorphisms represent a clinical concern.…”
Section: Pharmacogenetics Determinants Of Chemotherapy Toxicity In Acmentioning
confidence: 99%
“…16,17 Pharmacogene polymorphisms Studies have also explored the role of pharmacogene polymorphisms and how they affect GVHD incidence. 44 The methylene tetrahydrofolate reductase (MTHFR) gene is one of the more extensively studied pharmacogenes in relation to GVHD, and encodes an enzyme responsible for the metabolism of folate into folic acid, 18 which in turn is required for the de novo synthesis of thymidine. Drugs such as MTX inhibit this process, thus interfering with cell division.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%